Crystal structure of ethyl 4-{[5-(adamantan-1-yl)-2-sulfanylidene-2,3-dihydro-1,3,4-oxadiazol-3-yl]methyl}piperazine-1-carboxylate, C20H30N4O3S - Al-Sanea, Mohammad M.; Abdelbaky, Mohammed S. M.; Garcia-Granda, Santiago; Mohamed, Ahmed A. B.; Tiekink, Edward R. T. *; El-Eman, Ali A. (De Gruyter, 2023)
C20H30N4O3S, orthorhombic, P212121 (no. 19), a = 7.7152(3) Å, b = 10.6132(2) Å, c = 25.5990(7) Å, V = 2096.12(11) Å3, Z = 4, Rgt(F) = 0.0579, wRref(F2) = 0.1216, T = 293 K. CCDC no.: 2220806